The Possible Role of JC Polyomavirus after Kidney Transplantation - Haidar A Shamran (Journal of Global Pharma Technology, 2018)
Background John Cunningham virus (JCV) is one of the highly sero-prevalent viruses worldwide, and after primary infection it remains latent and then reactivates in immunocompromised patients, high JCV viruria seen in renal transplant recipients (RTR), some of them progress to polyomavirus associated nephropathy (PVAN). The objectives of this study are to determine JCV viruria and viremia in RTR and correlate them with urine cytology results and patients' renal function. Methods a prospective study conducted from October 2015 to to March 2016. Seventy-one (71) RTR, and 71 apparently healthy age and sex-matched normal donors as controls were enrolled in this study. Urine samples taken from all RTR cases and control, while plasma was taken from only 50 RTRs and 50 controls. Urine cytology smears were prepared and Pap-stained for decoy cells (DC) screening. Viral DNA was extracted from 1 ml urine, and from 200µl for plasma samples, and then the viral DNA was detected and measured by a real time-PCR instrument, using q RT-PCR kits for JC virus. Results Thirty one (43.70 %) of RTR and 10% of the controls were JC viruria positive, the mean of JCV viruria was 6.8 x104, and 1.04x103 copies/ml for RTRs and controls respectively (p<0.001), and 19/33 (57.58) of RTRs who had abnormal creatinine clearance were JC viruria positive (p=0.025). All 50 RTRs and the 20 controls had negative JC viremia. The rate of occurrence of DC in urine cytology was 28.17% for RTRs while none of the control subjects had DC in urine, but no correlation between JC viruria and the rate of decoy cell shedding in RTRs. Conclusion High prevalence of JCV viruria in RTRs, and associated with impairment of their renal function, which might suggest a pathological role of this virus have impact on renal function.Keywords: JC Polyomavirus, Kidney transplantation, Real-time PCR.